Tech-trekking with geocaching: unveiling the intersection of smartphone dependency and healthy wellbeing / Mohd Asmadzy Ahmad Basra - Ahmad Basra, Mohd Asmadzy (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Adventurers have been drawn to the realm of geocaching, a real-life treasure hunt that combines outdoor exploration and the thrill of discovery, for decades because of the thrill of the quest. However, this age-old activity has transformed digitally in today's tech-dominated world, with smartphones becoming an integral part of the hunt (Xu et al., 2017). The outcome? A spirited discussion about how to maintain our wellbeing while finding a balance between screen time and outdoor activities. Accepting the Electronic Treasure Map Imagine this: you can now locate hidden caches by using your reliable smartphone instead of just your map and compass. You only need a few taps to join a community of likeminded treasure hunters that can help you locate the elusive prize by providing you with interactive maps and exact coordinates. With this tech-savvy twist, geocaching is now more accessible and appealing than ever, attracting a new generation of modern adventurers eager to find hidden treasures in their backyard (Boys et al., 2017).